Mortality and Morbidity Risks and Economic Behavior - Stoler, Avraham (2012)
There are theoretical reasons to expect that high risk of mortality or morbidity during young adulthood decreases investment in human capital. However, investigation of this hypothesis is complicated by a variety of empirical challenges, including difficulties in inferring causation due to omitted variables and reverse causation. For example, to compare two groups with substantially different mortality rates, one typically has to use samples from different countries or time periods, making it difficult to control for other relevant variables. Reverse causation is important because human capital investment can affect mortality and morbidity. To counter these problems, we collected data on human capital investments, fertility decisions, and other economic choices of people at risk for Huntington’s disease. Huntington’s disease is a fatal genetic disorder that introduces a large and exogenous risk of early mortality and morbidity. We find a strong negative relation between mortality and morbidity risks and human capital investment.